A de jure study of social accountability for water and sanitation services in Uganda - Nansubuga, J.; Smith, Heather M.; Jeffrey, Paul (IWA Publishing, 2022)
The provision and sustainability of water and sanitation services in many countries is compromised by poor accountability for investment and maintenance programmes. Previous work has largely been concerned with processes, tools, and initiatives which support wider accountability without considering the ways in which accountability is formalised in law and regulations. We use a structured content analysis of 17 legislative and policy documents from Uganda to identify the evidence for de jure accountability across 21 key water and sanitation functions using the following four accountability themes: rules, process, and standards; responsibilities and duties; performance monitoring; and corrective measures, incentives, and sanctions. Results indicate that there is a strong provision for accountability across two of the four themes but also weaknesses relating to lack of complaint mechanisms, limited stakeholder engagement in regulation formulation, and weak performance monitoring. These findings are contextualised by reference to previous work in the field with particular emphasis on the discontinuities between legal requirements and local initiatives.
Keywords: legal requirements; social accountability; water and sanitation services